A crystal face regulation type electrolytic copper powder binary core-shell dispersant and a preparation method thereof
Patent Information
- Application Number
- CN202611147573.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]此外,现有相关技术中,水性涂料用有机硅助剂的作用目标与机制均不适用于电解铜粉的晶粒调控与分散稳定;纳米氧化物分散剂仅能实现已制备粉体的悬浮稳定,无法对电沉积的析铜结晶过程进行精准调控
[0029] The crystal-facet-controlled binary core-shell dispersant for electrolytic copper powder provided by this invention is a compound of isopropanolamine and Si-C bonded polyether-modified hydrolysis-resistant polysiloxane. Isopropanolamine can form multidentate coordination adsorption on the highly active crystal faces of newly formed copper, preferentially passivating the growth sites of high-index crystal faces, balancing the deposition rate of each crystal face, and inhibiting the formation of dendrites, burrs, and abnormally large particles, ensuring the copper powder has a regular morphology and uniform particle size. The Si-C bonded polyether-modified hydrolysis-resistant polysiloxane is connected by Si-C covalent bonds and will not undergo hydrolysis and bond breaking in weakly alkaline electrolytes. It spreads directionally on the outside of the isopropanolamine coordination layer to form a continuous and dense hydrophobic shell. This dispersant constructs a steric barrier, preventing copper particles from colliding and agglomerating while physically isolating dissolved oxygen from contacting the copper surface, effectively reducing oxygen content. The core-shell coating structure formed by the synergistic action of the binary components is stable and reliable, exhibiting excellent storage and cycling stability. Even after long-term recycling of the electrolyte, the effective component structure remains intact and the concentration is uniform. The relative standard deviation of particle size of multiple batches of electrolytic copper powder is significantly reduced, improving production batch stability, extending electrolyte lifespan, and reducing operating costs. At the same time, this dispersant is compatible with weakly alkaline cyanide-free electrolytic copper powder process systems, requiring no modification to existing electrolysis equipment and processes, demonstrating good process compatibility and ease of large-scale promotion.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrolytic copper powder technology, and relates to a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder and its preparation method. Background Technology
[0002] Electrolytic copper powder, with its advantages of high purity, good formability, and controllable particle size, is widely used in powder metallurgy, conductive pastes, electromagnetic shielding, and catalytic materials. As downstream industries increasingly demand fineness, uniformity, oxidation resistance, and batch stability of copper powder, regulating the electrocrystallization process of copper and inhibiting particle agglomeration through electrolyte additives has become crucial for producing high-quality electrolytic copper powder. During the electrolytic powdering process, dispersants, by adsorbing onto the surface of newly formed copper powder, regulate the crystal growth rate and construct interparticle repulsion barriers, directly determining the particle size distribution, morphological regularity, and oxygen content level of the product.
[0003] Existing electrolytic copper powder dispersion technologies mostly rely on traditional binary compound systems, typically combining triethanolamine with natural polymers such as animal glue and starch. These systems are only suitable for acidic electrolytic environments. When applied to weakly alkaline, cyanide-free electrolytic systems with a pH of 9.0–10.5, the protein components undergo hydrolytic degradation, leading to rapid failure of steric hindrance. Ordinary polymers exhibit poor film continuity and uneven coating, making it difficult to suppress the abnormal growth of highly active crystal faces. This easily induces dendrite formation, microscopic soft agglomeration, and interfacial bridging, resulting in a wide copper powder particle size distribution, uneven morphology, and high oxygen content. Furthermore, traditional compound dispersants are mostly simple physical mixtures, leading to poor system stability. Long-term cyclic use easily results in stratification and sedimentation, and the deactivation of effective components, causing large performance fluctuations between different batches of copper powder, failing to meet the requirements of large-scale, stable production.
[0004] Furthermore, in existing related technologies, the target and mechanism of action of organosilicon additives for water-based coatings are not applicable to the grain control and dispersion stability of electrolytic copper powder; nano-oxide dispersants can only achieve the suspension stability of the prepared powder and cannot accurately control the copper crystallization process of electrodeposition.
[0005] Therefore, developing a compound dispersant with strong alkali resistance, uniform coating, and the ability to simultaneously achieve precise grain size control and long-term stable dispersion is an urgent problem to be solved in the preparation of high-quality ultrafine electrolytic copper powder. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a crystal-facet-controlled binary core-shell dispersant for electrolytic copper powder and its preparation method. This crystal-facet-controlled binary core-shell dispersant is suitable for weakly alkaline, cyanide-free electrolytic copper powder systems with a pH of 9.0-10.5. Through the synergistic effect of crystal facet coordination passivation and hydrophobic film formation barrier, it can effectively inhibit copper dendrite growth and particle agglomeration, resulting in ultrafine copper powder with uniform particle size and low oxygen content. The dispersant exists in a stable composite colloidal form, exhibiting excellent hydrolysis resistance, and can significantly improve the electrolyte cycling stability and batch consistency of copper powder, making it suitable for industrial-scale production.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a crystal-face-controlled binary core-shell dispersant for electrolytic copper powder, wherein the crystal-face-controlled binary core-shell dispersant for electrolytic copper powder is compounded from isopropanolamine and Si-C bond type polyether modified hydrolysis-resistant polysiloxane.
[0009] The Si-C bonded polyether modified hydrolysis-resistant polysiloxane is a nonionic polymer, and the polyether side chain is connected to the polysiloxane main chain through Si-C covalent bonds.
[0010] The crystal-facet-controlled binary core-shell dispersant for electrolytic copper powder provided by this invention is a compound of isopropanolamine and Si-C bonded polyether-modified hydrolysis-resistant polysiloxane. Isopropanolamine can form multidentate coordination adsorption on the highly active crystal faces of newly formed copper, preferentially passivating the growth sites of high-index crystal faces, balancing the deposition rate of each crystal face, and inhibiting the formation of dendrites, burrs, and abnormally large particles, ensuring the copper powder has a regular morphology and uniform particle size. The Si-C bonded polyether-modified hydrolysis-resistant polysiloxane is connected by Si-C covalent bonds and will not undergo hydrolysis and bond breaking in weakly alkaline electrolytes. It spreads directionally on the outside of the isopropanolamine coordination layer to form a continuous and dense hydrophobic shell. This dispersant constructs a steric barrier, preventing copper particles from colliding and agglomerating while physically isolating dissolved oxygen from contacting the copper surface, effectively reducing oxygen content. The core-shell coating structure formed by the synergistic action of the binary components is stable and reliable, exhibiting excellent storage and cycling stability. Even after long-term recycling of the electrolyte, the effective component structure remains intact and the concentration is uniform. The relative standard deviation of particle size of multiple batches of electrolytic copper powder is significantly reduced, improving production batch stability, extending electrolyte lifespan, and reducing operating costs. At the same time, this dispersant is compatible with weakly alkaline cyanide-free electrolytic copper powder process systems, requiring no modification to existing electrolysis equipment and processes, demonstrating good process compatibility and ease of large-scale promotion.
[0011] In some embodiments, the molar ratio of ethylene oxide to propylene oxide in the polyether side chain of the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 2:1 to 4:1.
[0012] In some embodiments, the number average molecular weight of the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 1500~3000.
[0013] In some embodiments, the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is prepared by the following method: using hydrogen-containing polysiloxane as the main material and allyl-terminated ethylene oxide-propylene oxide copolymer polyether as the grafting monomer, it is prepared by hydrosilylation reaction under the action of a platinum-based catalyst, and the polyether side chain is covalently grafted to the polysiloxane main chain through propyl bridging Si-C covalent bonds.
[0014] In some embodiments, the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is prepared by the following method:
[0015] S1. Hydrogen-containing polydimethylsiloxane and terminal allyl polyether are dehydrated at 100℃~115℃ for 1h~2h under vacuum conditions to remove trace amounts of moisture; the molar ratio of ethylene oxide to propylene oxide in the terminal allyl polyether is 2:1~4:1, and the end is capped with methyl.
[0016] S2. In a protective atmosphere, xylene is used as an inert solvent, and isopropanol chloroplatinate solution is added as a catalyst. The reaction temperature is controlled at 80℃~110℃, and the reaction is maintained at this temperature for 3h~5h. Then the temperature is lowered to 50℃~60℃, and after post-treatment, the Si-C bond type polyether modified hydrolysis resistant polysiloxane is obtained.
[0017] In some embodiments, the mass ratio of the isopropanolamine to the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 4:1 to 5:1.
[0018] Secondly, the present invention provides a method for preparing a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder, the method comprising the following steps:
[0019] A dispersion was obtained by adding Si-C bond type polyether modified hydrolysis-resistant polysiloxane to an isopropanolamine solution; the dispersion was then subjected to ultrasonic dispersion and homogenization treatment to obtain the crystal facet-controlled electrolytic copper powder binary core-shell dispersant described in the first aspect.
[0020] In some embodiments, the solid content of the dispersion is 10wt% to 15wt%.
[0021] In some embodiments, the ultrasonic power of the ultrasonic dispersion is 200W~300W.
[0022] In some embodiments, the ultrasonic dispersion time is 10 min to 15 min.
[0023] In some embodiments, the pressure of the homogenization process is 60 MPa to 100 MPa.
[0024] For example, the application of the crystal-face-controlled electrolytic copper powder binary core-shell dispersant provided by the present invention includes: adding the crystal-face-controlled electrolytic copper powder binary core-shell dispersant to a weakly alkaline cyanide-free copper electrolyte with a pH value of 9 to 10.5, wherein the amount of the crystal-face-controlled electrolytic copper powder binary core-shell dispersant added is 50 mg / L to 150 mg / L.
[0025] Optionally, the weakly alkaline cyanide-free copper electrolyte uses copper sulfate as the main salt, sodium tartrate as the complexing agent, sodium sulfate as the supporting electrolyte, and borax as the buffer. For example, in the weakly alkaline cyanide-free copper electrolyte, the concentration of copper sulfate is 20 g / L to 40 g / L, the concentration of sodium tartrate is 80 g / L to 120 g / L, the concentration of sodium sulfate is 30 g / L to 60 g / L, and the concentration of borax is 15 g / L to 30 g / L.
[0026] Optionally, the parameters for preparing electrolytic copper powder by electrolyzing the weakly alkaline cyanide-free copper electrolyte can be: a current density of 200 A / m 2 ~350A / m 2 The temperature is 45℃~60℃, and the distance between the anode and cathode is 5cm~7cm.
[0027] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The crystal-facet-controlled binary core-shell dispersant for electrolytic copper powder provided by this invention is a compound of isopropanolamine and Si-C bonded polyether-modified hydrolysis-resistant polysiloxane. Isopropanolamine can form multidentate coordination adsorption on the highly active crystal faces of newly formed copper, preferentially passivating the growth sites of high-index crystal faces, balancing the deposition rate of each crystal face, and inhibiting the formation of dendrites, burrs, and abnormally large particles, ensuring the copper powder has a regular morphology and uniform particle size. The Si-C bonded polyether-modified hydrolysis-resistant polysiloxane is connected by Si-C covalent bonds and will not undergo hydrolysis and bond breaking in weakly alkaline electrolytes. It spreads directionally on the outside of the isopropanolamine coordination layer to form a continuous and dense hydrophobic shell. This dispersant constructs a steric barrier, preventing copper particles from colliding and agglomerating while physically isolating dissolved oxygen from contacting the copper surface, effectively reducing oxygen content. The core-shell coating structure formed by the synergistic action of the binary components is stable and reliable, exhibiting excellent storage and cycling stability. Even after long-term recycling of the electrolyte, the effective component structure remains intact and the concentration is uniform. The relative standard deviation of particle size of multiple batches of electrolytic copper powder is significantly reduced, improving production batch stability, extending electrolyte lifespan, and reducing operating costs. At the same time, this dispersant is compatible with weakly alkaline cyanide-free electrolytic copper powder process systems, requiring no modification to existing electrolysis equipment and processes, demonstrating good process compatibility and ease of large-scale promotion. Detailed Implementation
[0030] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0031] The "range" disclosed in this invention can be defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. This type of range definition can include or exclude endpoints; any endpoint can be independently included or excluded, and they can be arbitrarily combined, meaning any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for specific parameters, it is understood that ranges of 60~110 and 80~120 are also expected. Furthermore, if minimum range values 1 and 2 are listed, and maximum range values 3, 4, and 5 are also listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0" and "5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥2, it is equivalent to listing integers such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For instance, when a parameter is described as an integer selected from "2~10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0032] In this invention, "a combination of at least two" refers to a quantity greater than or equal to two, unless otherwise specified. For example, "any combination of one or at least two" means one or more or more items. It can be understood that when referring to "a combination of at least two," it refers to any suitable combination of multiple items, that is, a combination of "at least two" items carried out in a manner that does not conflict with and enables the implementation of this invention.
[0033] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0034] The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this invention can be combined with other embodiments.
[0035] Those skilled in the art will understand that the order in which the steps are written in the methods of the various embodiments does not imply a strict execution order. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, but are preferably performed sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), meaning that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0036] In this invention, open-ended technical features or solutions described using terms such as "comprising" do not exclude additional members beyond those listed unless otherwise specified. They can be considered as providing both closed-ended features or solutions comprised of the listed members and open-ended features or solutions that include additional members beyond the listed members. For example, A includes a1, a2, and a3. Unless otherwise specified, it may also include other members or exclude additional members. This can be considered as providing both technical features or solutions where "A is composed of a1, a2, and a3" or "A is selected from a1, a2, and a3," and technical features or solutions where "A includes not only a1, a2, and a3, but also other members."
[0037] In this invention, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a group consisting of A, B, and "a combination of A and B". "Containing A and / or B" can mean "containing A, containing B, and containing A and B", or "containing A, containing B, or containing A and B", and can be appropriately understood according to the context.
[0038] In this invention, the terms "first aspect," "second aspect," "third aspect," "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on the quantity.
[0039] In this invention, "optional" means that something is optional, that is, it refers to either "with" or "without". If there are multiple "optional" options in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, then each "optional" option is independent.
[0040] In this invention, "room temperature" generally refers to 4℃~35℃, and can refer to 20℃±5℃. In some embodiments of this invention, room temperature refers to 20℃~30℃.
[0041] In a first aspect, the present invention provides a crystal-face-controlled binary core-shell dispersant for electrolytic copper powder, wherein the crystal-face-controlled binary core-shell dispersant for electrolytic copper powder is compounded from isopropanolamine and Si-C bond type polyether modified hydrolysis-resistant polysiloxane.
[0042] The Si-C bonded polyether modified hydrolysis-resistant polysiloxane is a nonionic polymer, and the polyether side chain is connected to the polysiloxane main chain through Si-C covalent bonds.
[0043] The crystal-facet-controlled binary core-shell dispersant for electrolytic copper powder provided by this invention is a compound of isopropanolamine and Si-C bonded polyether-modified hydrolysis-resistant polysiloxane. Isopropanolamine can form multidentate coordination adsorption on the highly active crystal faces of newly formed copper, preferentially passivating the growth sites of high-index crystal faces, balancing the deposition rate of each crystal face, and inhibiting the formation of dendrites, burrs, and abnormally large particles, ensuring the copper powder has a regular morphology and uniform particle size. The Si-C bonded polyether-modified hydrolysis-resistant polysiloxane is connected by Si-C covalent bonds and will not undergo hydrolysis and bond breaking in weakly alkaline electrolytes. It spreads directionally on the outside of the isopropanolamine coordination layer to form a continuous and dense hydrophobic shell. This dispersant constructs a steric barrier, preventing copper particles from colliding and agglomerating while physically isolating dissolved oxygen from contacting the copper surface, effectively reducing oxygen content. The core-shell coating structure formed by the synergistic action of the binary components is stable and reliable, exhibiting excellent storage and cycling stability. Even after long-term recycling of the electrolyte, the effective component structure remains intact and the concentration is uniform. The relative standard deviation of particle size of multiple batches of electrolytic copper powder is significantly reduced, improving production batch stability, extending electrolyte lifespan, and reducing operating costs. At the same time, this dispersant is compatible with weakly alkaline cyanide-free electrolytic copper powder process systems, requiring no modification to existing electrolysis equipment and processes, demonstrating good process compatibility and ease of large-scale promotion.
[0044] In some embodiments, the molar ratio of ethylene oxide to propylene oxide in the polyether side chain of the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 2:1 to 4:1, for example, it can be 2:1, 3:1 or 4:1, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0045] In some embodiments, the number average molecular weight of the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 1500~3000, for example, it can be 1500, 1600, 1800, 2000, 2100, 2400, 2500, 2700, 2800 or 3000, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0046] In some embodiments, the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is prepared by the following method: using hydrogen-containing polysiloxane as the main material and allyl-terminated ethylene oxide-propylene oxide copolymer polyether as the grafting monomer, it is prepared by hydrosilylation reaction under the action of a platinum-based catalyst, and the polyether side chain is covalently grafted to the polysiloxane main chain through propyl bridging Si-C covalent bonds.
[0047] In some embodiments, the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is prepared by the following method:
[0048] S1. Hydrogen-containing polydimethylsiloxane and terminal allyl polyether are dehydrated at 100℃~115℃ for 1h~2h under vacuum conditions to remove trace amounts of moisture; the molar ratio of ethylene oxide to propylene oxide in the terminal allyl polyether is 2:1~4:1, and the end is capped with methyl.
[0049] S2. In a protective atmosphere, xylene is used as an inert solvent, and isopropanol chloroplatinate solution is added as a catalyst. The reaction temperature is controlled at 80℃~110℃, and the reaction is maintained at this temperature for 3h~5h. Then the temperature is lowered to 50℃~60℃, and after post-treatment, the Si-C bond type polyether modified hydrolysis resistant polysiloxane is obtained.
[0050] In some embodiments, the mass ratio of the isopropanolamine to the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 4:1 to 5:1, for example, it can be 4:1, 4.2:1, 4.4:1, 4.5:1, 4.8:1 or 5:1, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0051] Secondly, the present invention provides a method for preparing a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder, the method comprising the following steps:
[0052] A dispersion was obtained by adding Si-C bond type polyether modified hydrolysis-resistant polysiloxane to an isopropanolamine solution; the dispersion was then subjected to ultrasonic dispersion and homogenization treatment to obtain the crystal facet-controlled electrolytic copper powder binary core-shell dispersant described in the first aspect.
[0053] In some embodiments, the solid content of the dispersion is 10wt% to 15wt%, for example, it can be 10wt%, 12wt%, 13wt%, 14wt% or 15wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0054] In some embodiments, the ultrasonic power of the ultrasonic dispersion is 200W to 300W, for example, it can be 200W, 210W, 220W, 240W, 250W, 270W, 280W or 300W, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0055] In some embodiments, the ultrasonic dispersion time is 10 min to 15 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0056] In some embodiments, the homogenization pressure is 60 MPa to 100 MPa, for example, 60 MPa, 70 MPa, 80 MPa, 90 MPa or 100 MPa, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0057] For example, the application of the crystal-face-controlled electrolytic copper powder binary core-shell dispersant provided by the present invention includes: adding the crystal-face-controlled electrolytic copper powder binary core-shell dispersant to a weakly alkaline cyanide-free copper electrolyte with a pH value of 9 to 10.5, wherein the amount of the crystal-face-controlled electrolytic copper powder binary core-shell dispersant added is 50 mg / L to 150 mg / L.
[0058] Optionally, the weakly alkaline cyanide-free copper electrolyte uses copper sulfate as the main salt, sodium tartrate as the complexing agent, sodium sulfate as the supporting electrolyte, and borax as the buffer. For example, in the weakly alkaline cyanide-free copper electrolyte, the concentration of copper sulfate is 20 g / L to 40 g / L, the concentration of sodium tartrate is 80 g / L to 120 g / L, the concentration of sodium sulfate is 30 g / L to 60 g / L, and the concentration of borax is 15 g / L to 30 g / L.
[0059] Optionally, the parameters for preparing electrolytic copper powder by electrolyzing the weakly alkaline cyanide-free copper electrolyte can be: a current density of 200 A / m 2 ~350A / m 2The temperature is 45℃~60℃, and the distance between the anode and cathode is 5cm~7cm.
[0060] Preparation Example 1
[0061] This preparation example provides a method for preparing Si-C bonded polyether modified hydrolysis-resistant polysiloxanes, including:
[0062] S1. Hydrogen-containing polydimethylsiloxane and terminal allyl polyether are dehydrated at 110°C for 1.5 h under vacuum to remove trace amounts of moisture; the molar ratio of ethylene oxide to propylene oxide in the terminal allyl polyether is 3:1, and the end is capped with methyl groups.
[0063] S2. Under a nitrogen atmosphere, based on a molar ratio of Si-H bonds to C=C double bonds in the terminal allyl polyether of 1:1.3, dehydrated hydrogen-containing polydimethylsiloxane (active hydrogen content 0.25wt%, number average molecular weight 800) and terminal allyl polyether (number average molecular weight 600) were dissolved in xylene. Isopropanol chloroplatinate solution was added as a catalyst, and the reaction temperature was controlled at 100℃ for 4 hours. Then, the temperature was lowered to 55℃, and xylene and low-boiling substances were removed by vacuum distillation to obtain the Si-C bond type polyether modified hydrolysis-resistant polysiloxane.
[0064] The obtained Si-C bond type polyether modified hydrolysis-resistant polysiloxane is a nonionic polymer, and the polyether side chain is connected to the polysiloxane main chain through Si-C covalent bonds; and the molar ratio of ethylene oxide to propylene oxide in the polyether side chain of the Si-C bond type polyether modified hydrolysis-resistant polysiloxane is 3:1; the number average molecular weight of the Si-C bond type polyether modified hydrolysis-resistant polysiloxane is 2200.
[0065] Preparation Example 2
[0066] This preparation example provides a method for preparing Si-C bonded polyether modified hydrolysis-resistant polysiloxanes, including:
[0067] S1. Hydrogen-containing polydimethylsiloxane and terminal allyl polyether are dehydrated at 100°C for 2 hours under vacuum to remove trace amounts of moisture; the molar ratio of ethylene oxide to propylene oxide in the terminal allyl polyether is 2:1, and the end is capped with methyl groups.
[0068] S2. Under a nitrogen atmosphere, based on a molar ratio of Si-H bonds to C=C double bonds in the terminal allyl polyether of 1:1.2, dehydrated hydrogen-containing polydimethylsiloxane (active hydrogen content 0.25wt%, number average molecular weight 700) and terminal allyl polyether (number average molecular weight 500) were dissolved in xylene. Isopropanol chloroplatinate solution was added as a catalyst, and the reaction temperature was controlled at 80℃ for 5 hours. Then, the temperature was lowered to 50℃, and xylene and low-boiling substances were removed by vacuum distillation to obtain the Si-C bond type polyether modified hydrolysis-resistant polysiloxane.
[0069] The obtained Si-C bond type polyether modified hydrolysis-resistant polysiloxane is a nonionic polymer, and the polyether side chain is connected to the polysiloxane main chain through Si-C covalent bonds; and in the polyether side chain of the Si-C bond type polyether modified hydrolysis-resistant polysiloxane, the molar ratio of ethylene oxide to propylene oxide is 2:1; the number average molecular weight of the Si-C bond type polyether modified hydrolysis-resistant polysiloxane is 1500.
[0070] Preparation Example 3
[0071] This preparation example provides a method for preparing Si-C bonded polyether modified hydrolysis-resistant polysiloxanes, including:
[0072] S1. Hydrogen-containing polydimethylsiloxane and terminal allyl polyether are dehydrated at 115°C for 1 hour under vacuum to remove trace amounts of moisture; the molar ratio of ethylene oxide to propylene oxide in the terminal allyl polyether is 4:1, and the end is capped with methyl groups.
[0073] S2. Under a nitrogen atmosphere, based on a molar ratio of Si-H bonds to C=C double bonds in the terminal allyl polyether of 1:1.4, dehydrated hydrogen-containing polydimethylsiloxane (active hydrogen content 0.25wt%, number average molecular weight 950) and terminal allyl polyether (number average molecular weight 800) were dissolved in xylene. Isopropanol chloroplatinate solution was added as a catalyst, and the reaction temperature was controlled at 110℃ for 3 hours. Then, the temperature was lowered to 60℃, and xylene and low-boiling substances were removed by vacuum distillation to obtain the Si-C bond type polyether modified hydrolysis-resistant polysiloxane.
[0074] The obtained Si-C bond type polyether modified hydrolysis-resistant polysiloxane is a nonionic polymer, and the polyether side chain is connected to the polysiloxane main chain through Si-C covalent bonds; and the molar ratio of ethylene oxide to propylene oxide in the polyether side chain of the Si-C bond type polyether modified hydrolysis-resistant polysiloxane is 4:1; the number average molecular weight of the Si-C bond type polyether modified hydrolysis-resistant polysiloxane is 3000.
[0075] Example 1
[0076] This embodiment provides a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder, which is compounded from isopropanolamine and the Si-C bond type polyether modified hydrolysis-resistant polysiloxane provided in Preparation Example 1;
[0077] The mass ratio of isopropanolamine to Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 4.5:1.
[0078] In this embodiment, the preparation method of the crystal plane-controlled electrolytic copper powder binary core-shell dispersant includes:
[0079] A dispersion with a solid content of 12 wt% was obtained by adding Si-C bond type polyether modified hydrolysis-resistant polysiloxane to an isopropanolamine solution; the dispersion was then subjected to ultrasonic dispersion and homogenization treatment to obtain a crystal facet-controlled electrolytic copper powder binary core-shell dispersant.
[0080] The ultrasonic dispersion power is 250W, and the time is 12min;
[0081] The homogenization process is performed at a pressure of 80 MPa.
[0082] Example 2
[0083] This embodiment provides a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder, which is compounded from isopropanolamine and the Si-C bond type polyether modified hydrolysis-resistant polysiloxane provided in Preparation Example 1;
[0084] The mass ratio of isopropanolamine to Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 4:1.
[0085] In this embodiment, the preparation method of the crystal plane-controlled electrolytic copper powder binary core-shell dispersant includes:
[0086] A dispersion with a solid content of 10 wt% was obtained by adding Si-C bond type polyether modified hydrolysis-resistant polysiloxane to an isopropanolamine solution; the dispersion was then subjected to ultrasonic dispersion and homogenization treatment to obtain a crystal facet-controlled electrolytic copper powder binary core-shell dispersant.
[0087] The ultrasonic dispersion has an ultrasonic power of 200W and a duration of 15 minutes.
[0088] The homogenization process is performed at a pressure of 60 MPa.
[0089] Example 3
[0090] This embodiment provides a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder, which is compounded from isopropanolamine and the Si-C bond type polyether modified hydrolysis-resistant polysiloxane provided in Preparation Example 1;
[0091] The mass ratio of isopropanolamine to Si-C bond type polyether modified hydrolysis-resistant polysiloxane is 5:1.
[0092] In this embodiment, the preparation method of the crystal plane-controlled electrolytic copper powder binary core-shell dispersant includes:
[0093] A dispersion with a solid content of 15 wt% was obtained by adding Si-C bond type polyether modified hydrolysis-resistant polysiloxane to an isopropanolamine solution; the dispersion was then subjected to ultrasonic dispersion and homogenization treatment to obtain a crystal facet-controlled electrolytic copper powder binary core-shell dispersant.
[0094] The ultrasonic dispersion has an ultrasonic power of 300W and a duration of 10 minutes;
[0095] The homogenization process is performed at a pressure of 100 MPa.
[0096] Example 4
[0097] This embodiment provides a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder. Except for the mass ratio of isopropanolamine to Si-C bond type polyether modified hydrolysis-resistant polysiloxane being 3:1, everything else is the same as in Example 1.
[0098] Example 5
[0099] This embodiment provides a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder. Except for the mass ratio of isopropanolamine to Si-C bond type polyether modified hydrolysis-resistant polysiloxane being 6:1, all other aspects are the same as in Example 1.
[0100] Example 6
[0101] This embodiment provides a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder. Except for the Si-C bond type polyether modified hydrolysis-resistant polysiloxane provided in Preparation Example 2, the rest are the same as in Example 1.
[0102] Example 7
[0103] This embodiment provides a crystal plane-controlled binary core-shell dispersant for electrolytic copper powder. Except for the Si-C bond type polyether modified hydrolysis-resistant polysiloxane provided in Preparation Example 3, the rest are the same as in Example 1.
[0104] Comparative Example 1
[0105] This comparative example provides a dispersant, which is isopropanolamine as described in Example 1.
[0106] Comparative Example 2
[0107] This comparative example provides a dispersant, which is the Si-C bonded polyether modified hydrolysis-resistant polysiloxane of Example 1.
[0108] Performance Characterization
[0109] The crystal-facet-controlled electrolytic copper powder binary core-shell dispersant provided in the above embodiments and the dispersant provided in the comparative example were added to a weakly alkaline cyanide-free copper electrolyte with a pH of 10. The amount of the crystal-facet-controlled electrolytic copper powder binary core-shell dispersant added was 100 mg / L. In the weakly alkaline cyanide-free copper electrolyte, the concentrations of copper sulfate, sodium tartrate, sodium sulfate, and borax were 30 g / L, 100 g / L, 45 g / L, and 20 g / L, respectively. The parameters for preparing electrolytic copper powder by electrolyzing the weakly alkaline cyanide-free copper electrolyte were: a current density of 300 A / m³. 2The temperature was 50℃, and the distance between the anode and cathode was 6cm. The median particle size (D50), particle size distribution span, and oxygen content of the obtained electrolytic copper powder were measured, and the results are shown in Table 1.
[0110] Among them, the median particle size D50 and the particle size span were determined by a laser particle size analyzer, and span = (D90-D10) / D50; the dried copper powder samples were tested by an infrared oxygen analyzer to directly determine the total oxygen content of the powder. All test samples were electrolytic copper powder that had been washed with pure water and thoroughly dried after electrolysis.
[0111] Table 1
[0112]
[0113] As can be seen from Examples 1 to 3, 6 and 7 in Table 1, when the crystal facet-controlled binary core-shell dispersant for electrolytic copper powder provided by the present invention is used to prepare weakly alkaline cyanide-free electrolytic copper powder, the resulting copper powder has a concentrated D50 distribution and low oxygen content. It can achieve synergy between crystal facet control and core-shell coating, effectively suppress dendrite and abnormal growth, and obtain electrolytic copper powder with regular morphology, uniform particle size and low oxidation.
[0114] Comparison of Comparative Examples 1 and 2 with Example 1 shows that although isopropanolamine alone can form coordination adsorption on the copper crystal surface, it lacks the physical barrier effect of the hydrophobic shell of polysiloxane. The newly formed copper particles collide and agglomerate severely in the electrolyte, and at the same time, it fails to effectively isolate dissolved oxygen, resulting in large particle size and increased oxygen content. Polysiloxane alone can encapsulate particles, but due to the lack of preferential passivation of highly active crystal surfaces by isopropanolamine, it cannot suppress the growth of dendrites and burrs. The particle morphology is irregular, and the coating layer is directly attached to the unmodified crystal surface, resulting in poor compactness, which leads to a significant increase in span and oxygen content.
[0115] A comparison of Examples 4 and 5 with Example 1 shows that in Example 4, the relative excess of isopropanolamine and the insufficient amount of polysiloxane resulted in poor continuity of the hydrophobic shell, weakened steric barrier, ineffective isolation between particles, increased product span, and increased oxygen content. In Example 5, the proportion of polysiloxane was further reduced, the outer coating of the coordination layer was incomplete, the passivation effect of the crystal plane was relatively weakened, the dendrite suppression effect was worse, and the oxygen content increased.
[0116] In summary, the crystal-facet-controlled binary core-shell dispersant for electrolytic copper powder provided by this invention is a compound of isopropanolamine and Si-C bonded polyether-modified hydrolysis-resistant polysiloxane. Isopropanolamine can form multidentate coordination adsorption on the highly active crystal faces of newly formed copper, preferentially passivating the growth sites of high-index crystal faces, balancing the deposition rate of each crystal face, and inhibiting the formation of dendrites, burrs, and abnormally large particles, ensuring the copper powder has a regular morphology and uniform particle size. The Si-C bonded polyether-modified hydrolysis-resistant polysiloxane is connected by Si-C covalent bonds and will not undergo hydrolysis and bond breaking in weakly alkaline electrolytes. It spreads directionally on the outside of the isopropanolamine coordination layer, forming a continuous and dense hydrophobic layer. The outer shell forms a steric barrier, preventing copper particles from colliding and agglomerating while physically isolating dissolved oxygen from contacting the copper surface, effectively reducing oxygen content. The core-shell coating structure formed by the synergistic action of the binary components is stable and reliable, exhibiting excellent storage and cycling stability. Even after long-term recycling of the electrolyte, the effective component structure remains intact and the concentration is uniform. The relative standard deviation of particle size of multiple batches of electrolytic copper powder is significantly reduced, improving production batch stability, extending electrolyte lifespan, and reducing operating costs. At the same time, this dispersant is compatible with weakly alkaline cyanide-free electrolytic copper powder process systems, requiring no modification to existing electrolysis equipment and processes, demonstrating good process compatibility and ease of large-scale promotion.
[0117] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A binary core-shell dispersant for electrolytic copper powder with crystal plane regulation, characterized in that, The crystal plane-controlled electrolytic copper powder binary core-shell dispersant is composed of isopropanolamine and Si-C bond type polyether modified hydrolysis-resistant polysiloxane; The Si-C bonded polyether modified hydrolysis-resistant polysiloxane is a nonionic polymer, and the polyether side chain is connected to the polysiloxane main chain through Si-C covalent bonds.
2. The crystal plane-controlled electrolytic copper powder binary core-shell dispersant according to claim 1, characterized in that, In the polyether side chain of the Si-C bonded polyether modified hydrolysis-resistant polysiloxane, the molar ratio of ethylene oxide to propylene oxide is 2:1 to 4:
1.
3. The crystal plane-controlled electrolytic copper powder binary core-shell dispersant according to claim 1 or 2, characterized in that, The number average molecular weight of the Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 1500~3000.
4. The crystal plane-controlled binary core-shell dispersant for electrolytic copper powder according to any one of claims 1 to 3, characterized in that, The Si-C bond-type polyether modified hydrolysis-resistant polysiloxane is prepared by the following method: using hydrogen-containing polysiloxane as the main material and allyl-terminated ethylene oxide-propylene oxide copolymer polyether as the grafting monomer, it is prepared by hydrosilylation reaction under the action of platinum catalyst. The polyether side chain is covalently grafted to the polysiloxane main chain through propyl bridging Si-C covalent bonds.
5. The crystal plane-controlled electrolytic copper powder binary core-shell dispersant according to claim 4, characterized in that, The Si-C bonded polyether modified hydrolysis-resistant polysiloxane was prepared by the following method: S1. Hydrogen-containing polydimethylsiloxane and terminal allyl polyether are dehydrated at 100℃~115℃ for 1h~2h under vacuum conditions to remove trace amounts of moisture; the molar ratio of ethylene oxide to propylene oxide in the terminal allyl polyether is 2:1~4:1, and the end is capped with methyl. S2. In a protective atmosphere, xylene is used as an inert solvent, and isopropanol chloroplatinate solution is added as a catalyst. The reaction temperature is controlled at 80℃~110℃, and the reaction is maintained at this temperature for 3h~5h. Then the temperature is lowered to 50℃~60℃, and after post-treatment, the Si-C bond type polyether modified hydrolysis resistant polysiloxane is obtained.
6. The crystal plane-controlled electrolytic copper powder binary core-shell dispersant according to any one of claims 1 to 5, characterized in that, The mass ratio of isopropanolamine to Si-C bonded polyether modified hydrolysis-resistant polysiloxane is 4:1 to 5:
1.
7. A method for preparing a binary core-shell dispersant for electrolytic copper powder with crystal plane regulation, characterized in that, The preparation method includes the following steps: A dispersion is obtained by adding Si-C bond type polyether modified hydrolysis-resistant polysiloxane to an isopropanolamine solution; the dispersion is then subjected to ultrasonic dispersion and homogenization treatment to obtain the crystal facet-controlled electrolytic copper powder binary core-shell dispersant as described in any one of claims 1 to 6.
8. The preparation method according to claim 7, characterized in that, The solid content of the dispersion is 10wt%~15wt%.
9. The preparation method according to claim 7 or 8, characterized in that, The ultrasonic power of the ultrasonic dispersion is 200W~300W; And / or, the ultrasonic dispersion time is 10 min to 15 min.
10. The preparation method according to any one of claims 7 to 9, characterized in that, The homogenization process is carried out at a pressure of 60 MPa to 100 MPa.